High-risk Allele for Herpes Labialis Severity at the IFNL3/4 Locus is Associated With Vestibular Neuritis - Rujescu, Dan; Herrling, Marko; Hartmann, Annette M.; Maul, Stephan; Giegling, Ina; Konte, Bettina; Strupp, Michael (Frontiers in Neurology, 2020)
Objective: Vestibular neuritis (VN) is a peripheral vestibular disorder leading to a sudden loss of unilateral vestibular function. Although the underlying etiological mechanisms for disease development are not yet known, there is evidence that a latent infection with herpes simplex virus type 1 (HSV-1) might be involved. The polymorphism rs12979860 has been associated with the severity of recurrent herpes labialis and hepatitis C virus (HCV) clearance and treatment outcome and is located within the first intron of the IFNL4 gene on chromosome 19.q13.2. This case control study was conducted to evaluate the association of rs12979860 with VN occurrence. Methods: DNA was extracted from EDTA blood of 151 VN patients and 1775 healthy controls. Genotyping of rs12979860 was performed using iPLEX and MassARRAY Matrix Assisted Laser Desorption Ionization – Time of Flight (MALDI-TOF) mass spectrometry. For association analyses, an additive, dominant and recessive logistic regression model was calculated, using age and sex as covariates. Results: A significant association of rs12979860 with VN was obtained for the additive (OR=1.51 (1.18 – 1.92); p=9.23 x 10-4) and dominant models (OR=2.15 (1.48 – 3.13); p=5.86 x 10-5), with the T allele being more frequent in the VN group. Conclusion: By detecting a significant association of the rs12979860-T risk allele for herpes labialis severity with susceptibility to VN, this study gives further indirect evidence for an involvement of HSV-1 in VN pathology, thereby strengthening the virus hypothesis.